The Boxers, China, and the World - Bickers, Robert; Tiedemann, R. G. (Rowman & Littlefield Publishers, 2007)
In 1900, China chose to take on imperialism by fighting a war with the world on the parched north China plain. This multidisciplinary volume explores the causes behind what is now known as the Boxer War, examining its particular cruelties and its impact on China, foreign imperialism in China, and on the foreign imagination. This war introduced the world to the "Boxers," the seemingly fanatical, violent xenophobes who, believing themselves invulnerable to foreign bullets, died in their thousands in front of foreign guns. But 1900 also saw the imperialism of the 1890s checked and the Qing rulers of China move to embark on a series of shattering reforms. The Boxers have often been represented as a force from China's past, resisting an enforced modernity. Here, expert contributors argue that this rebellion was instead a wholly modern resistance to globalizing power, representing new trends in modern China and in international relations. The allied invasion of north China in late summer 1900 was the first multinational intervention in the name of "civilization," with the issues and attendant problems that have become all too familiar in the early twenty-first century. Indeed, understanding the Boxer rising and the Boxer war remains a pressing contemporary issue. This volume will appeal to readers interested in modern Chinese, East Asian, and European history as well as the history of imperialism, colonialism, warfare, missionary work, and Christianity. Contributions by: C. A. Bayly, Lewis Bernstein, Robert Bickers, Paul A. Cohen, Henrietta Harrison, James L. Hevia, Ben Middleton, T. G. Otte, Roger R. Thompson, R. G. Tiedemann, and Anand A. Yang.